Wettability improvement of pea protein isolate agglomerated in pulsed fluid bed. (18th May 2020) - Nascimento, Raul Favaro; Rosa, Juliana Gomes; Andreola, Kaciane; Taranto, Osvaldir Pereira
Abstract: The pea protein isolate (PPI) is characterized as a cohesive powder, presenting channeling formation during its fluidization (Geldart type A) and reduced dispersion in water. This work aimed at agglomerating the PPI for the production of an instant product. The process was carried out in a pulsed fluid bed and gum Arabic was used as a liquid binder. Seven tests were performed according to a full-factorial design, where the independent variables were fluidizing air temperature (65–85 °C) and binder flow rate (2.4–3.8 mL/min). Moisture content, process yield, and mean particle size were analyzed as responses. Furthermore, wetting time and flowability were compared before and after the agglomeration between raw and agglomerate PPI. Product transformations were also evaluated by analysis of size distribution, porosity, wetting time, flowability, and shape parameters. When compared to raw material, agglomerated particles had larger granules with a moisture content below 5.0% and process yield above 60.7%, as well as better flowability, a more regular shape, lower porosity, and a 99% reduction in wetting time.